The history of islam in the Malay archipelago : an analytical study of Abdullah Bin Nuh 's works Mohammad Noviani Ardi - Ardi, Muhammad Noviandi; Abdullah, Fatimah (IIUM Press, 2018)
the topic on the coming of Islam to the Malay world has become anintellectual debate among scholars around the world for both Muslimand Western scholars. There are at least four elements of debate onthese issues, in particular, on the originality of Islamic doctrines inthe Malay world, the theory of the coming of Islam to the Malayworld, the times of the coming of Islam as well as the spreading ofIslam in the Nusantara. This research will be on attempt inexplicating Abdullah bin Nuh’s works particularly in his discourses of the coming of Islam to the Nusantara. It focuses on three works by Abdullah bin Nuh, entitled Sejarah Islam di Jawa Barat hingga Zaman Keemasan Banten, Ringkasan Sejarah Wali Songo, al-IslāmFi Indūnīsiyyā, and his articles delivered in the Seminar on The Advent of Islam in Indonesia held in Medan in 1963. The approach of this study is based on textual analysis, using descriptive, analyticalmethods from various works of the subject under study, comparisonand contrast in order to get additional information from the otherulama’ in the same era as Abdullah bin Nuh. This study concludesthat Abdullah bin Nuh believes that Islam came to Nusantara inparticular to Indonesia since 7th century CE even though there is aclaim that says Islam came much earlier from the Arab Peninsulaplus encounters the theory most of Western scholars who view thatIslam came in 12th century CE.